2010
DOI: 10.4103/0974-7788.72485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Withania somnifera (Ashwagandha) and Terminalia arjuna (Arjuna) on physical performance and cardiorespiratory endurance in healthy young adults

Abstract: Introduction:Several medicinal plants have been described to be beneficial for cardiac ailments in Ayurveda like Ashwagandha and Arjuna. Ashwagandha-categorised as Rasayanas, and described to promote health and longevity and Arjuna primarily for heart ailments. coronary artery disease, heart failure, hypercholesterolemia, anginal pain and can be considered as a useful drug for coronary artery disease, hypertension and ischemic cardiomyopathy.Objective:There are no scientific clinical studies showing effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 8 publications
8
55
0
Order By: Relevance
“…W. somnifera is categorized as Rasayanas and is proposed to promote health and longevity, while Arjuna is primarily used for heart ailments such as coronary artery disease, heart failure, hypercholesterolemia, anginal pain and can be considered as a useful drug for coronary artery disease, hypertension and ischemic cardiomyopathy (Sandhu et al 2010).…”
Section: Effects Of W Somnifera On Various Cardiovascular Diseasesmentioning
confidence: 99%
“…W. somnifera is categorized as Rasayanas and is proposed to promote health and longevity, while Arjuna is primarily used for heart ailments such as coronary artery disease, heart failure, hypercholesterolemia, anginal pain and can be considered as a useful drug for coronary artery disease, hypertension and ischemic cardiomyopathy (Sandhu et al 2010).…”
Section: Effects Of W Somnifera On Various Cardiovascular Diseasesmentioning
confidence: 99%
“…The pharmacological studies suggested that W. somnifera improves the athletic performance via increasing the hemoglobin count and red blood cell count, which leads to an increase in the capacity of blood to transport oxygen at a greater capacity to the peripheral system (Shenoy et al, 2012). It has been shown that W. somnifera improves endurance performance in healthy individuals at a moderate intensity of 65% VO2 max (Sandhu, 2010). W. somnifera which is rich in proteins, amino acids (glycine, alanine, tyrosine, aspartic acid, tryptophan, glutamic acid, cysteine, etc.…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…Enhanced physical performance and cardiorespiratory endurance in healthy young adult human beings (Sandhu et al, 2010).…”
Section: Withania Somniferamentioning
confidence: 99%